They Really Like Us!: Move From Outputs to Outcomes with Your Library's Research Consultations - Wanucha, Meghan (My University, 2017)
Learn how librarians at East Carolina took an evidence-based approach to those academic library standbys: one-on-one research consultations. This poster presentation will share our experiences developing a post-meeting survey, results and next steps, and best practices for how you could do the same at your library.
Keywords: academic libraries